2018
DOI: 10.1155/2018/3189879
|View full text |Cite
|
Sign up to set email alerts
|

Stevia Nonsweetener Fraction Displays an Insulinotropic Effect Involving Neurotransmission in Pancreatic Islets

Abstract: Stevia rebaudiana (Bert.) Bertoni besides being a source of noncaloric sweeteners is also an important source of bioactive molecules. Many plant extracts, mostly obtained with ethyl acetate solvent, are rich in polyphenol compounds that present insulinotropic effects. To investigate whether the nonsweetener fraction, which is rich in phenolic compounds isolated from Stevia rebaudiana with the solvent ethyl acetate (EAF), has an insulinotropic effect, including interference at the terminals of the autonomic ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The larger gastrocnemius and soleus muscle pads may explain, at least in part, the enhanced load-carrying capacity of these rats. It is possible that the insulinotropic effects of S. rebaudiana [32] enhanced the whey protein-induced protein synthesis in these skeletal muscles, as suggested by the higher levels of insulinemia found in those rats (Table 3). However, further studies are necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The larger gastrocnemius and soleus muscle pads may explain, at least in part, the enhanced load-carrying capacity of these rats. It is possible that the insulinotropic effects of S. rebaudiana [32] enhanced the whey protein-induced protein synthesis in these skeletal muscles, as suggested by the higher levels of insulinemia found in those rats (Table 3). However, further studies are necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Stevioside, which is the major compound of S. rebaudiana Bertoni, has the effect of stimulating insulin secretion and increasing insulin sensitivity by acting directly on pancreatic beta cells. (28,29) Another study showed that S. rebaudiana Bertoni extract increased the expression of peroxisome proliferatoractivated receptor-γ (PPARγ) and insulin mRNA. (8) PPARγ plays an important role in maintaining glucose metabolism by stimulating glucokinase and GLUT2 in the pancreas and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Stevia aqueous extract significantly increased the fasting serum insulin leveland this finding is in the same side with jeppesen et al, (2002) 29 they stated that Steviosides could increase insulin secretion by direct action on beta cells. Recently, Piovan et al, (2018) found thatethyl acetate fraction of stevia increased insulin secretion in presence of high glucose concentration. This insulinotropic effect may be attributed to an enhancement of cholinergic and attenuation of adrenergic inhibitory effects on glucose stimulated insulin secretion with a result of an increase in insulin levels in the blood 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Piovan et al, (2018) found thatethyl acetate fraction of stevia increased insulin secretion in presence of high glucose concentration. This insulinotropic effect may be attributed to an enhancement of cholinergic and attenuation of adrenergic inhibitory effects on glucose stimulated insulin secretion with a result of an increase in insulin levels in the blood 30 .…”
Section: Discussionmentioning
confidence: 99%